Constitutional regulation and financing of elections - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A.; Сотула, Олександр Сергійович; Сотула, О. С.; Сотула, Александр Сергеевич; Sotula, Oleksandr S.; Латковський, Павло Павлович; Латковський, П. П.; Латковский, Павел Павлович; Latkovskyi, Pavlo P.; et al. (Editorial Primmate S. A. S., 2019)
The article focuses on problems of constitutional regulation of elections and requirements for candidates for representative positions in a democratic society. The issue of financing elections and solutions for this problem were considered, taking into account the "financial" qualification that was set at the legislative level in many democratic states of the world. The terminology that is present in the constitutional legal science concerning the regulation of elections is analyzed, the stages in the election process are considered and the main problems that occur during this process are revealed. In the course of the study of the topic, the author concludes on the need for financial control and monitoring of expenditures from the state budget during the electoral process, not only to detect a violation of legislation or to identify financial crimes, but also to determine the profitability of the electoral process as a whole, for its reformation and to reduce budget expenses during the elections. Also, the author comes to the conclusion that it is necessary to bring the financial qualification to the financial capability of all citizens of the state for each subsequent election, proceeding from the official minimum and average salaries.

Статтю присвячено розгляду проблем конституційно-правового регулювання виборів та критеріям до кандидатів на представницькі посади демократичного суспільства. Також була розглянута проблематика фінансування виборів та шляхи вирішення такої проблеми, з урахуванням «фінансового» цензу, який на законодавчому рівні встановлений в багатьох демократичних державах світу. Проаналізована термінологія, яка присутня в конституційно-правовій науці щодо регулювання виборів, розглянуті етапи виборчого процесу та виявлені основні проблеми, які викають під час такого процесу. В процесі дослідження теми статі, автор приходить до висновку щодо необхідності фінансового контролю та моніторингу витрат з державного бюджету під час виборчого процесу не тільки на виявлення порушення законодавства чи виявлення фінансових злочинів, а ще й на рентабельність виборчого процесу в цілому, задля його реформування та зниження бюджетних витрат на вибори. Також, автор доходить до висновку про необхідність приведення фінансового цензу до відповідності фінансових можливостей усіх громадян держави на кожні послідуючі вибори, відштовхуючись від офіційно встановлених мінімальних та середніх заробітних плат.
Latkovska T. Constitutional regulation and financing of elections / Latkovska T., Sotula O., Latkovskyy P., Hlynianyi I. // Amazonia Investiga. – Vol. 8. - Issue 20. – Editorial Primmate S. A. S., 2019. – P. 365-375.
Keywords: constitutional regulation; electoral process; electoral rights; electoral subject; stages in the electoral process; financing of elections; financial monitoring; financial electoral qualification; конституційно-правове регулювання; виборчий процес; виборчі права; суб’єкти виборчого процесу; етапи виборчого процесу; фінансування виборів; фінансовий моніторинг; фінансовий виборчий ценз; Research Subject Categories::LAW/JURISPRUDENCE